(untitled) (Salam International Academic Journal, 2025)
The migration of Afghans abroad is a complex and multidimensional phenomenon that has emerged as a result of prolonged war, political instability, and economic crises, leading millions of individuals to leave their homeland. This study investigates the key factors influencing Afghan migration, the economic and social consequences of this trend, and the opportunities it may create. Taking into account the social, economic, and political realities that Afghan migrants face, the study analyzes the challenges, potential benefits, and the role of the Afghan government in managing this process. The research employs a qualitative approach and is based on library research. Data collection was conducted using credible academic sources, reports published by international organizations, and other reliable references. In addition to the literature review, interviews were conducted with Afghan migrants residing in Iran and Turkey to enrich the dataset and allow for field-level analysis of their perspectives and lived experiences. Purposeful interviews with selected migrants were also used to help identify the psychological impacts of migration. The findings indicate that a range of economic, social, political, and security-related factors contribute to Afghan migration. The results of this study can support the development of effective policies aimed at reducing irregular migration, improving the conditions of Afghan migrants in host countries, and leveraging the opportunities that migration may offer.